Eocene Araucaria Sect. Eutacta from Patagonia and floristic turnover during the initial isolation of South America - Rossetto Harris, Gabriella; Wilf, Peter; Escapa, Ignacio Hernán; Andruchow Colombo, Ana (American Journal of Botany)
Premise: Eocene floras of Patagonia document biotic response to the final separation of Gondwana. The conifer genus Araucaria, distributed worldwide during the Mesozoic, has a disjunct extant distribution between South America and Australasia. Fossils assigned to Australasian Araucaria Sect. Eutacta usually are represented by isolated organs, making diagnosis difficult. Araucaria pichileufensis E.W. Berry, from the middle Eocene Río Pichileufú (RP) site in Argentine Patagonia, was originally placed in Sect. Eutacta and later reported from the early Eocene Laguna del Hunco (LH) locality. However, the relationship of A. pichileufensis to Sect. Eutacta and the conspecificity of the Araucaria material among these Patagonian floras have not been tested using modern methods. Methods: We review the type material of A. pichileufensis alongside large (n = 192) new fossil collections of Araucaria from LH and RP, including multi-organ preservation of leafy branches, ovuliferous complexes, and pollen cones. We use a total evidence phylogenetic analysis to analyze relationships of the fossils to Sect. Eutacta. Results: We describe Araucaria huncoensis sp. nov. from LH and improve the whole-plant concept for Araucaria pichileufensis from RP. The two species respectively resolve in the crown and stem of Sect. Eutacta. Conclusions: Our results confirm the presence and indicate the survival of Sect. Eutacta in South America during early Antarctic separation. The exceptionally complete fossils significantly predate several molecular age estimates for crown Eutacta. The differentiation of two Araucaria species demonstrates conifer turnover during climate change and initial South American isolation from the early to middle Eocene. Fil: Rossetto Harris, Gabriella. State University of Pennsylvania; Estados Unidos Fil: Wilf, Peter. State University of Pennsylvania; Estados Unidos Fil: Escapa, Ignacio Hernán. Museo Paleontológico Egidio Feruglio; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina ...